Neferet's curse - Cast, P. C. (House of night novellas, 2013)
"The White City, 1893: In turn-of-the-century Chicago, with the World's Fair bringing bustle and excitement to her home city, sixteen-year-old Emily Wheiler should be reveling in her youthful beauty and the excitement around her. But her whole life changed when her mother died, leaving her to be the Lady of Wheiler House. Her father, a powerful bank president, is at the center of an important social hub for the booming young city, and he needs Emily to do everything her mother would have - to be a good hostess and make sure the mansion runs smoothly. As Emily uneasily tries to replace her mother, she also longs for more... for love and a life of her own. When a handsome young man notices her at one of her father's parties, it seems that her hopes may finally be coming true. Until her father forbids her to see him - or any other man - and starts revealing a darkly violent side that even he can't understand. At last, afraid for her life and with nowhere to turn, Emily is Marked by a vampyre and brought to the Chicago House of Night, where she begins a magickal new life that should allow the wounds from her past to heal. But as she gains strength, and a powerful new name, she carries a dark need to wreak vengeance on the man she trusted most. From victim to High Priestess, beautiful young woman to powerful seductress, Neferet's journey begins in NEFERET'S CURSE.."--